Development of a preliminary environmental risk assessment system by using text mining for introducing alien crops. (1st June 2022) - Hong, Yooinn; Lee, Minhyun; Rim, Hojun; Do, Yuno; Kim, Seong-Cheol; Bang, Jeong Hwan; Song, Uhram
Abstract: Changes in worldwide crop trends and climate change has increased the introduction of alien crops. However, there are always potential side effect issues related to introduced crops, such as the introduced crop becoming a nuisance at the new country or bringing insect pests or microorganisms with the introduced crops. In this study, we developed a crop introduction risk assessment system using text mining method to prevent this problem. First, we designed the "Preliminary Environmental Impact Assessment Index for Alien Crops" based on ecological researches to assess the risks of introduced crops to the natural environment. The questionaries evaluate the target alien crop with previous cases reporting the target crops' adverse effects on the environment, the potential of target crops' direct or indirect damage on the environment. The index has sixteen questions with allocated scores that are divided into 4 categories. The detailed rationales of the questionaries and the assessment index are discussed in main text. Second, we assessed 67 crop species that were introduced or scheduled to be introduced to South Korea with this Preliminary Assessment Index. The literature and data were collected with JabRef, search engines, and from the documents of six international institutions. Finally, based on the preliminary assessment results of selected species, we developed the protocols and a manual for the preliminary environmental risk assessment of introduced species. Final evaluation scores for risk evaluation for introducing crops are suggested (over 70 total score for 'danger' and over 50 points for 'caution required', and under 50 points for 'low expected impact'). Presented crop introduction risk assessment system is effective to identify potential problem making crop species. The protocols and a manual that we provide in this study could be applied to other countries which have similar climate and environmental conditions, or after being adequately modified to their environmental factors such as climate, neighboring countries, major crops according to eating habits, and major vegetation. Highlights: A crop introduction risk assessment system using text mining method is studied. Preliminary environmental impact assessment index for alien crops are developed. Protocols for the preliminary risk assessment of introduced species are suggested. Presented system is effective to identify potential problem making crop species.